Binding in working memory and frontal lobe in normal aging: is there any similarity with autism? - Lecouvey, Grégory; Quinette, Peggy; Kalpouzos, Grégoria; Guillery-Girard, Bérengère; Bejanin, Alexandre; Gonneaud, Julie; Abbas, Ahmed; Viader, Fausto; Eustache, Francis; Desgranges, Béatrice (Frontiers in Human Neuroscience, 2015)
Some studies highlight similarities between Autism Spectrum Disorder (ASD) and healthy aging. Indeed, the decline in older individuals’ ability to create a unified representation of the individual features of an event is thought to arise from a disruption of binding within the episodic buffer of working memory (WM) as the same way as observed in ASD. In both cases, this deficit may result from an abnormal engagement of a frontohippocampal network. The objective of the present study is to identify both cognitive processes and neural substrates associated with the deficit of binding in WM in healthy aging. We studied the capacity of binding and the cognitive processes that might subtend its decline in 72 healthy participants aged 18–84 years. We examined the behavioral data in relation to the changes in brain metabolism associated with the age-related decline in a subgroup of 34 healthy participants aged 20–77 years using the resting-state [18F] fluorodeoxyglucose positron emission tomography (18F-FDG PET). Forward stepwise regression analyses showed that the age-related decline in binding was partially explained by a decline in inhibition and processing speed. PET correlation analyses indicated that metabolism of the frontal regions, anterior and middle cingulate cortices is implicated in this phenomenon. These data suggest that executive functions and processing speed may play a crucial role in the capacity to integrate unified representations in memory in aging. Possible implications are discussed in ASD.